Valoración económica del bosque protector la cascada como alternativa para la gestión sostenible del ecosistema forestal en el Cantón El Chaco, Provincia Del Napo. Año 2016 - Cifuentes Molina, Maritza del Carmen (2016)
“La Cascada” Protected Forest is located in the East of Ecuador, In the Gonzalo Diaz de Pineda Parish, In the Chaco Canton, in the Napo Province. It encompass 31,000 ha. of forest included in the category denominated as Tropical rain forest of the Amazon and is a pristine habitat of flora and fauna. This forest system provides environmental goods and services such as storage of a large amount of biomass, thereby preserving the physical and biological environment, accumulating abundant carbon, keeping the water balance, biodiversity and chemical-nutritional characteristics of the soil, as well as its scenic beauty. Many forest related environmental goods and services that affect the welfare of human beings, the environment and the economy do not have a commercial or economic value, so they have no real recognized value nor is their importance, yield and role obvious. Economic valuation of the La Cascada Protected Forest is the 282.908 US, which is based on specific quantitative and economic measurement for each good or service from its ecosystem, allows us to see it as an asset through sustainable management thus avoiding the indiscriminate use of resources contained therein and guiding the actions that help to protect it for the future.